Reconstructing Identity through Spice Route Narrative:: An Urgency for Nation Branding? - Dewi Kumoratih (Journal of Visual Art and Design, 2022)
In line with Joko Widodo's vision to position Indonesia as the ‘Global Maritime Fulcrum’ by 2045, the Indonesian government through the Ministry of Education and Culture has initiated the proposal of nominating the Spice Route (Jalur Rempah) as World Heritage in 2017 to UNESCO. This article aims to show the dynamic process of redefining national identity through the Spice Route narrative, which is full of contestation between the state, society, and the market. Previous studies have shown that the process of reproduction of nationalism through the reconstruction of national history and national identity is now no longer always initiated by the elite. Democratization and globalization also provide space for civil society to reinterpret their ideal image of Indonesia. Methods used in this qualitative research included auto-ethnography through participant observation, in-depth interviews, literature studies, comparison, and visual communication design analysis of form-content-context, both descriptively and reflectively. In conclusion, instead of being a political-ideological narrative, the Spice Route narrative is reinterpreted in a new domain: the creative industry. It has become a source of inspiration for branding commercial products, feature films and documentaries, community activities, festivals, educational curricula, and at the same time included in the content of Indonesian cultural diplomacy through gastronomy, all of which require a contribution of design. This article examines the extent to which the Spice Route narrative, seemingly intended as a nation brand, is able to reconstruct and redefine the national identity of Indonesia.